Metric evidences of the Rosenberg Self-Esteem Scale in higher education students in the city of Tacna - Nuñez Delgado, Rocio del Pilar (2021)
The present research work aims to determine the psychometric properties of the Rosenberg self-esteem scale; It is instrumental, involving a sample with 115 higher education students from Tacna between 18 to 55 years old. Item analysis, exploratory analysis, confirmatory analysis, bifactor, parallel analysis, reliability were performed and percentiles were determined. The results indicate that items 6 and 8 are not adequate for the negative dimension and this same dimension is not adequate according to the total variance explained; In the confirmatory analysis, the GFI adjustment index was not optimal, the parallel analysis using the least squares method recommends two dimensions and explains 59% of the explained variance, it was analyzed according to the adjustment indices for a bifactor that cannot be a one-dimensional scale.